ENDOSULFAN INDUCED ALTERATIONS IN THE GONAD OF TWO FRESHWATER MUSSELS IN DIFFERENT SEASONS - MULEY, D. V.; MANE, U. H. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Endosulfan caused more or less similar type of effects on both, male and female gonads Lamellidens corrianus and L. marginalis in monsoon and winter, but the severity of effect w more in summer. Comparatively, it was observed that the female follicles of L. corriants a male follicles of L. marginalis were more affected in all the seasons.